‘Determinism’ Is Just Fine: A Reply to Scott Sehon - De Marco, G (Springer, 2016)
Scott Sehon recently argued that the standard notion of determinism employed in the Consequence Argument makes it so that, if our world turns out to be deterministic, then an interventionist God is logically impossible. He further argues that because of this, we should revise our notion of determinism. In this paper I show that Sehon’s argument for the claim that the truth of determinism, in this sense, would make an interventionist God logically impossible ultimately fails. I then offer and respond to a weaker version of the argument for the claim that we should revise our notion of determinism.